The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.2147/ijn.s374293
|View full text |Cite
|
Sign up to set email alerts
|

ICAM1-Targeting Theranostic Nanoparticles for Magnetic Resonance Imaging and Therapy of Triple-Negative Breast Cancer

Abstract: Purpose Owing to the lack of effective biomarkers, triple-negative breast cancer (TNBC) has the worst prognosis among all subtypes of breast cancer. Meanwhile, tremendous progress has been made to identify biomarkers for TNBC. However, limited number of biomarkers still restrain the specifically targeting outcomes against TNBC. Here, to solve the obstacle, we designed and synthesized a new type of biocompatible nanoparticles to amplify the targeting effects for TNBC theranostics. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…Theranostic nanoparticles modified with anti-ICAM1 target could specifically target TNBC in an in vitro experiment by Chen et al. ( 53 ). However, a recent study found that ICAM1-deficient breast cancer cells develop large metastatic lesions ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…Theranostic nanoparticles modified with anti-ICAM1 target could specifically target TNBC in an in vitro experiment by Chen et al. ( 53 ). However, a recent study found that ICAM1-deficient breast cancer cells develop large metastatic lesions ( 54 ).…”
Section: Discussionmentioning
confidence: 99%
“…To address this issue, vesicular NPs with poly­(ethylene glycol)-poly­(ε-caprolactone) copolymers conjugate anti-ICAM1 antibodies using click chemistry. These NPs have shown enhanced diagnostic and therapeutic efficacy in tumor models, with extended circulation time, and additionally in vitro experiments exhibited specific targeting action specifically for TNBC . Theranostic NPs offer multiple therapeutic applications, including tumor-targeting imaging, focused ultrasound ablation, chemotherapy, and sonodynamic therapy.…”
Section: Therapeutic Interventions Involving Nanocarriers For Managem...mentioning
confidence: 99%
“…These NPs have shown enhanced diagnostic and therapeutic efficacy in tumor models, with extended circulation time, and additionally in vitro experiments exhibited specific targeting action specifically for TNBC. 134 Theranostic NPs offer multiple therapeutic applications, including tumor-targeting imaging, focused ultrasound ablation, chemotherapy, and sonodynamic therapy. A multimodal synergistic therapy can enhance TNBC treatment efficacy and prognosis by enhancing imaging, guided ablation, and focused ultrasound (FUS)/chemotherapy effects.…”
Section: Therapeutic Interventions Involving Nanocarriers For Managem...mentioning
confidence: 99%
“…Because only 1% of the intravenously injected nanomaterials could enter the tumour through the EPR (enhanced permeability and retention) effect, [39][40][41] we injected the nanomaterials directly into the tumour in order to achieve better imaging results. 42,43 Eu 3+ @L-Arg nanomaterials (62.5 mg mL −1 , 50 mL) were injected into the tumours of TUBO and 4T1 at day 5, 10 and 15 aer implantation of tumour cells. T2 and CEST scanning were undertook before and aer the injection.…”
Section: Cest Imaging Ability Of Eu 3+ @L-arg In Vivomentioning
confidence: 99%